Influence Current Ratio, Debt to Equity Ratio and Total Asset Turnover on Return on Equity in the Transportation Sector Industry - Qahfi Romula Siregar; Defi Desvita Harahap (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Sumatera Utara, 2021)
His study aims to determine whether there is an effect of Current Ratio, Debt To Equity Ratio, and Total Assets Turnover on Return On Equity in transportation sector companies listed on the Indonesia Stock Exchange. The approach used is an associative approach. The population in this study are retail trade sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. Samples were taken using purposive sampling method in order to obtain 7 companies as samples. And using multiple linear regression analysis methods, classical assumption test, t test (partial test), f test (simultaneous test) and coefficient of determination with the help of software SPSS V.20 (Statistical Product and Service Solutions). Based on the research results, it can be concluded that partially Total Assets Turnover has a significant effect on Return On Equity, while Current Ratio, Debt To Equity Ratio have no and insignificant effect on Return On Equity. And simultaneously Current Ratio, Debt To Equity Ratio, and Total Assets Turnover have a significant effect on Return On Equity in Transportation sector companies listed on the Indonesia Stock Exchange for the period 2015-2019.